STRATEGI MANAJEMEN KEPALA SEKOLAH DALAM PENGEMBANGAN BAKAT SISWA DI SD INPRES PANAIKANG - Nabila, Anugrah Rezky; Lestari, Fika; Arianti, Dini; Yuspiani, Yuspiani (Department of Islamic Education Management, 2026)
This study aims to describe the principal’s management strategies in developing student talents at SD Inpres Panaikang, focusing on the stages of planning, organizing, implementing, and controlling. The research employed a qualitative approach with a case study design. Data were collected through observations, interviews, and documentation involving the principal, teachers, and students. The findings reveal that student talent development at SD Inpres Panaikang has been managed systematically. In the planning stage, the principal identified students’ talents through teacher observations and formulated extracurricular and competition mentoring programs during school work meetings. In the organizing stage, a talent development team was established with a clear organizational structure and task distribution based on teachers’ competencies. Implementation was carried out through routine extracurricular activities, such as scouting, sports, and arts, as well as intensive mentoring for students with specific talents. The controlling stage involved regular monitoring and evaluation of student participation and achievement outcomes. Supporting factors included the strong commitment of the principal, teacher support, and collaboration with parents and the school committee. Meanwhile, limited facilities and training time were identified as inhibiting factors. This study concludes that effective student talent development is highly dependent on the principal’s ability to apply management functions in an integrated and sustainable manner, supported by collaboration among all school stakeholders.